Characterization and expression of a cDNA encoding the human androgen receptor. - Tilley, W D (1989)
We report the isolation of a cDNA that encodes the complete human androgen receptor. The cDNA predicts a protein of 917 amino acids with a molecular weight of 98,918. Introduction of the cDNA into heterologous mammalian cells caused expression of high levels of a protein that binds dihydrotestosterone with the affinity, specificity, and sedimentation properties characteristic of the native human androgen receptor. Comparisons with the amino acid sequence of previously cloned steroid hormone receptors revealed a high degree of sequence conservation with the progesterone, glucocorticoid, and mineralocorticoid receptors in the putative hormone and DNA-binding domain regions.